Nurses' Knowledge in Implementing Standard Operating Procedures on Patient Safety in Regional Public Hospitals - Suminar, Saka; Rusnita, Rusnita; Wisma Sari, Sinta; Hanung Lidiana, Exda; Rino Vanchapo, Antonius; Saleh Dunggio, Abdul Rivai; Rosida, Rosida (International Journal of Health Sciences, 2023)
Patient safety has become a global issue that is very important to be implemented by every hospital, and should be a top priority to be implemented and it is related to the quality and image of the hospital. With the development of science and technology in health services, especially in hospitals, it makes health service procedures more complex and has the potential for unexpected events or adverse events. The purpose of this study was to determine the relationship between nurses' knowledge in implementing Standard Operating Procedures on safety from the impact of falling patients in the treatment room of the Regional General Hospital. The research method used in this study is quantitative with an analytic survey research design using a cross sectional approach, which is a type of research for each research subject only once and measurements are made of the character status or subject variables at the time of the examination. Based on the results of the analysis, univariate analysis has been carried out on each variable to produce a frequency distribution and bivariate analysis to see the relationship between the independent variable and the dependent variable. Where the statistical test used is the Chi-Square test and the alternative test is Fisher's Exact. The conclusion is that there is a relationship between the level of nurse knowledge, nurse attitudes, nurse skills and nurse compliance with Standard Operating Procedures in the Regional General Hospital room.